2008
DOI: 10.1097/ccm.0b013e31816443cb
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of various metabolites to the “unmeasured” anions in critically ill patients with metabolic acidosis*

Abstract: Amino acids, uric acid, and organic acids together accounted for only 7.9% of the SIG in intensive care unit patients with metabolic acidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 24 publications
1
38
0
1
Order By: Relevance
“…In this setting, SIG likely represents unmeasured strong anions. They accumulate in sepsis, renal failure and organ dysfunction, but their origin and chemical nature is only partially understood [14,15]. Increased glycolysis, protein catabolism, mitochondrial dysfunction and decreased clearance likely contribute to their accumulation.…”
Section: Substance Removal and Reversal Of Hypotensionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this setting, SIG likely represents unmeasured strong anions. They accumulate in sepsis, renal failure and organ dysfunction, but their origin and chemical nature is only partially understood [14,15]. Increased glycolysis, protein catabolism, mitochondrial dysfunction and decreased clearance likely contribute to their accumulation.…”
Section: Substance Removal and Reversal Of Hypotensionmentioning
confidence: 99%
“…Increased glycolysis, protein catabolism, mitochondrial dysfunction and decreased clearance likely contribute to their accumulation. Potential candidates include sulfate, urate, hydroxybutyrate, succinate, pyroglutamate, D-lactate and Krebs cycle intermediates, but also components of drugs, nutrients or synthetic colloids [15][16][17][18]. However, despite using elaborate techniques to determine the components of SIG, the majority of its determinants are not yet identified [15].…”
Section: Substance Removal and Reversal Of Hypotensionmentioning
confidence: 99%
“…30 Whereas several other studies had demonstrated that delay of academia recovery as opposed to initial pH value was associated with increased mortality in the ICU. 31,32 In our study, we were able to demonstrate that pH was able to predict the risk of death with a RR of 2.94 (CI, 1.14-7.59) In our study we had found that hypoalbuminemia (serum albumin <3.5 g/dl) were present in 101/140 (72%) of all patients and 24/26 (92.3%) of those who had died. Hypoalbuminemia as a predictor of mortality with a RR of 4.8 (95% CI, 1.02 -23.1), PPV 21.8%, NPV 93.3%.…”
Section: 22mentioning
confidence: 66%
“…However, this speculation remains to be proven. Other possibilities include increased negatively charged acute phase proteins,36 or exogenous compounds in administered fluids (lactate, acetate, citrate, gluconate)39 or medications (anion‐containing β‐lactam antibiotics, parenteral nutrition)40 administered before hospital admission. However, because the retrospective design of this study we were unable to comment beyond this.…”
Section: Discussionmentioning
confidence: 99%